+0  
 
0
36
2
avatar

Solve for x:
(3x + 12)(3x + 4) = (4x^2 + 8x + 18x^2)/(2x).

 Nov 1, 2022
 #1
avatar+1025 
+1

Open up paranthesis by FOILing: 9x^2 + 36x + 12x + 48 = (4x^2 + 8x + 18x^2)/2x

Combine like terms: 9x^2 + 48x + 48 = (22x^2 + 8x)/2x

Factor out top and bottom by 2x, then cancel terms: (22x^2 + 8x)/2x = 2x(11x + 4)/2x = 11x + 4

9x^2 + 48x + 48 = 11x + 4

Combine like terms: 9x^2 + 37x + 44 = 0

Use quadratic formula: \({-37\pm\sqrt{37^2 - (4)(9)(44)}}\over18\) = \({-37 \pm\sqrt{1369 - 1584}}\over18\) = \(-37\pm i\sqrt{215}\over18\) = x

 Nov 1, 2022
 #2
avatar
0

Your answer is wrong.

Guest Nov 6, 2022

16 Online Users

avatar